2012
DOI: 10.3354/meps09853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water temperature and pH on growth and metabolite biosynthesis of coral reef sponges

Abstract: Warmer, more acidic water resulting from increased emissions of greenhouse gases will impact coral reef organisms, but the effects remain unknown for many dominant groups such as sponges. To test for possible effects, adult sponges of 6 common Caribbean coral reef speciesAiolochroia crassa, Aplysina cauliformis, Aplysina fistularis, Ectyoplasia ferox, Iotrochota birotulata and Smenospongia conulosa -were grown for 24 d in seawater ranging from values experienced at present-day summer-maxima (temperature = 28°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 58 publications
4
63
0
Order By: Relevance
“…In a similar species, Cliona celata, attachment to bivalve shells was slower in reduced pH treatments, and survival slightly depressed (Duckworth and Peterson 2012); however, this study lowered pH using hydrochloric acid, not by injecting CO 2 . It is possible that the reduced pH might have had a negative physiological effect on the sponges themselves, although there was no observed sponge mortality in this study, and others have reported limited impacts of pCO 2 on sponge physiology (Duckworth et al 2012;Wisshak et al 2012;Fang et al 2013). Despite no significant differences in attachment rates among treatments, sponge bioerosion was significantly increased in the high pCO 2 treatments.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…In a similar species, Cliona celata, attachment to bivalve shells was slower in reduced pH treatments, and survival slightly depressed (Duckworth and Peterson 2012); however, this study lowered pH using hydrochloric acid, not by injecting CO 2 . It is possible that the reduced pH might have had a negative physiological effect on the sponges themselves, although there was no observed sponge mortality in this study, and others have reported limited impacts of pCO 2 on sponge physiology (Duckworth et al 2012;Wisshak et al 2012;Fang et al 2013). Despite no significant differences in attachment rates among treatments, sponge bioerosion was significantly increased in the high pCO 2 treatments.…”
Section: Discussionmentioning
confidence: 60%
“…Target pH values for this system were 8.0 (ambient pCO 2 ), 7.8 (moderate pCO 2 ) and 7.6 (high pCO 2 ). In each reservoir, pH was monitored continuously using a pH controller (reef Fanatic) connected to a CO 2 regulator (Milwaukee Ma957); whenever pH levels exceeded the target values of 7.8 and 7.6 for the moderate and high pCO 2 treatments, respectively (anthony et al 2008;Duckworth et al 2012), the controller opened a valve that delivered CO 2 gas to the reservoir until target values were achieved again. no direct CO 2 manipulations occurred in the ambient pCO 2 reservoir.…”
Section: Study Species Collectionmentioning
confidence: 99%
See 3 more Smart Citations